Land-use change and Biogeochemical controls of soil CO2, N2O and CH4 fluxes in Cameroonian forest landscapes - Verchot, Louis V.; Dannenmann, Michael; Kengdo, S.K.; Njine-Bememba, C.B.; Rufino, Mariana C.; Sonwa, D.J.; Tejedor, J. (Informa UK Limited, 2020)
Deforestation and land-use change are accelerating in the Congo Basin and elsewhere in the tropics affecting the soil-atmosphere exchange of greenhouse gases (GHG). There is a lack of data from Central Africa. We quantified fluxes of CO2, CH4, and N2O at the soil-atmosphere interface in a secondary forest, a cocoa agroforest, and an unfertilized cropland. Soil respiration was highest in the secondary forest (15.37 ± 3.42 Mg C ha−1 y−1), intermediate in the cacao agroforest (12.26 ± 2.91 Mg C ha−1 y−1) and the lowest in the unfertilized cropland (8.74 ± 2.62 Mg C ha−1 y−1). Likewise, N2O fluxes were highest in the secondary forest (2.17 ± 0.20 kg N ha−1 y−1), intermediate in the cacao agroforest (1.40 ± 0.08 kg N ha−1 y−1) and lowest in the unfertilized cropland (1.04 ± 0.15 kg N ha−1 y−1). Soils were a sink for atmospheric CH4 and sink strength was high in the secondary forest (−3.60 ± 1.83 kg CH4 ha−1 y−1) and cacao agroforest (−3.61 ± 2.09 kg CH4 ha−1 y−1) and low in the unfertilized cropland (−1.9 ± 1.59 kg CH4 ha−1 y−1). Variation in soil water content rather than temperature was the dominant driver of seasonal variations of the fluxes at all study sites and N availability affected both N2O and CH4 fluxes. Our results suggest that tropical land-use change is decreasing soil respiration, decreasing the strength of the soil CH4 sink and decreasing N2O emissions, in landscapes that do not practice agriculture with chemical fertilization.